Comment on "Between emptiness and reality: from the white space in Chinese painting to the philosophy of form in western art" - Qing Li (Trans/Form/Ação)
Commented article: WANG, L.; WANG, B. Q. Between emptiness and reality: from the white space in Chinese painting to the philosophy of form in western art. Trans/Form/Ação: Unesp journal of philosophy, Marília, SP, v. 48, n. 3, p. e025010, 2025. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/16396.